Solving Boundary Value Problems For Linear Neutral Delay Differential-Difference Equations Using a Spline Collocation Method - Cherevko, Igor; Dorosh, Andrii; Haiuk, Ivan; Pertsov, Andriy (My University, 2022)
In this work, an iterative scheme using cubic splines with defect two is considered for a boundary value problem for neutral delay linear differential-difference equations.